GASP. XV. A MUSE view of extreme ram-pressure stripping along the line of sight: physical properties of the jellyfish galaxy JO201. Issue 1 (17th February 2019) - Bellhouse, Callum; Jaffé, Y L; McGee, S L; Poggianti, B M; Smith, R; Tonnesen, S; Fritz, J; Hau, G K T; Gullieuszik, M; Vulcani, B; Fasano, G; Moretti, A; et al.
Abstract: We present a study of the physical properties of JO201, a unique disc galaxy with extended tails undergoing extreme ram-pressure stripping (RPS) as it moves through the massive cluster Abell 85 at supersonic speeds mostly along the line of sight. JO201 was observed with multi-unit spectroscopic explorer as part of the GASP programme. In a previous paper (GASP II) we studied the stellar and gas kinematics. In this paper we present emission-line ratios, gas-phase metallicities, and ages of the stellar populations across the galaxy disc and tails. We find that while the emission at the core of the galaxy is dominated by an active galactic nucleus (AGN), the disc is composed of star-forming knots surrounded by excited diffuse gas. The collection of star-forming knots presents a metallicity gradient steadily decreasing from the centre of the galaxy outwards, and the ages of the stars across the galaxy show that the tails formed ≲10 9 yr ago. This result is consistent with an estimate of the stripping time-scale (∼1 Gyr), obtained from a toy orbital model. Overall, our results independently and consistently support a scenario in which a recent or ongoing event of intense RPS acting from the outer disc inwards, causes removal and compression of gas, thus altering the AGN and star formation activity within and around the galaxy.